2020
DOI: 10.17645/mac.v8i2.2853
|View full text |Cite
|
Sign up to set email alerts
|

Third-Person Perceptions and Calls for Censorship of Flat Earth Videos on YouTube

Abstract: Calls for censorship have been made in response to the proliferation of flat Earth videos on YouTube, but these videos are likely convincing to very few. Instead, people may worry these videos are brainwashing others. That individuals believe other people will be more influenced by media messages than themselves is called third-person perception (TPP), and the consequences from those perceptions, such as calls for censorship, are called third-person effects (TPE). Here, we conduct three studies that examine th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…First, belief in conspiracy theories about vaccines/vaccination is a significant predictor, being associated with lower levels of TPE perception about media's influence on vaccination against COVID-19. These results contradict our expectations based on the literature to date (Douglas and Sutton, 2008; Landrum and Olshanky, 2020), stating that conspiratorial thinking might be correlated with high TPE, that is, people tend to believe that others are more prone to be affected by conspiracy theories circulating in the media. Findings from this study show a different kind of influence – the more people believe in conspiracy theories related to COVID-19 vaccination, the less they perceive others to be more influenced by the media on COVID-19 vaccination topics, thus invalidating H2.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…First, belief in conspiracy theories about vaccines/vaccination is a significant predictor, being associated with lower levels of TPE perception about media's influence on vaccination against COVID-19. These results contradict our expectations based on the literature to date (Douglas and Sutton, 2008; Landrum and Olshanky, 2020), stating that conspiratorial thinking might be correlated with high TPE, that is, people tend to believe that others are more prone to be affected by conspiracy theories circulating in the media. Findings from this study show a different kind of influence – the more people believe in conspiracy theories related to COVID-19 vaccination, the less they perceive others to be more influenced by the media on COVID-19 vaccination topics, thus invalidating H2.…”
Section: Resultscontrasting
confidence: 99%
“…Other investigations (Islam et al, 2021;Jolley and Douglas, 2014;Lewandowsky et al, 2013) indicated that a negative attitude towards vaccination can be linked to belief in conspiracy theories on the matter. Conspiratorial thinking is reportedly correlated with TPE, that is, people tend to believe that others are more prone to be affected by conspiracy theories (Douglas and Sutton, 2008;Landrum and Olshansky, 2020). However, to our knowledge, there is no academic study published so far reflecting to what extent TPE materializes in the context of conspiracy theories about COVID-19 vaccines.…”
Section: Predictors Of Third-person Perceptionsmentioning
confidence: 97%
“…The third-person effect may have both negative and positive societal outcomes. On the one hand, the third-person effect may fuel a demand for harmful regulations, as people who display a stronger perceptual gap in undesirable media effects are more likely to support censorship (e.g., Olshansky & Landrum, 2020; although meta-analytical evidence suggest that the effect size is small at best Feng & Guo, 2012). On the other hand, the third-person effect motivates actions to protect vulnerable others (Barnidge & Rojas, 2014;Lim, 2017), which may include the correction of misinformation (Koo et al, 2021).…”
Section: Perceived Danger Of Misinformationmentioning
confidence: 99%
“…One of the most prominent consequences of the self-other gap in perceived media influence (i.e. TPP) is support for restrictive or protective actions such as censorship of flat Earth videos on YouTube (Olshansky and Landrum, 2020) or Internet privacy protection measures (Chen and Atkin, 2021). In the context of misinformation, social media platform regulation has been widely discussed as the behavioral outcome of TPP.…”
Section: Consequences Of Tpp: Government Regulation Versus Content Mo...mentioning
confidence: 99%